2023
DOI: 10.3390/jcm12041435
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Refraction and Visual Function of Novel Perifocal Ophthalmic Lens for the Control of Myopia Progression

Abstract: This study aimed to evaluate the peripheral defocus induced with a novel perifocal ophthalmic lens for myopia progression control and the potential impact on visual function. This experimental, non-dispensing crossover study evaluated 17 myopic young adults. The peripheral refraction was measured using an open-field autorefractor, at 2.50 m from the target point, in two eccentric points, 25° temporal, 25° nasal, and central vision. Visual contrast sensitivity (VCS) was measured at 3.00 m with a Vistech system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A wearer trial showed efficiency results similar to those for the defocus-incorporated multiple segments (DIMS) lens 44,45 (see the next section), with data available for 4 to 5 years since the start of wear 44 . As would be expected, the lens is successful in reducing peripheral relative hyperopia along the horizontal visual field 21,66,67 …”
Section: Progressive Addition Lenses Developed For Myopia Treatmentmentioning
confidence: 73%
See 1 more Smart Citation
“…A wearer trial showed efficiency results similar to those for the defocus-incorporated multiple segments (DIMS) lens 44,45 (see the next section), with data available for 4 to 5 years since the start of wear 44 . As would be expected, the lens is successful in reducing peripheral relative hyperopia along the horizontal visual field 21,66,67 …”
Section: Progressive Addition Lenses Developed For Myopia Treatmentmentioning
confidence: 73%
“…44 As would be expected, the lens is successful in reducing peripheral relative hyperopia along the horizontal visual field. 21,66,67 The Apollo lens is mentioned by Li et al 46 The full addition power of 2.50 D occurs superiorly, with 80 and 60% of this achieved nasally and temporally, respectively.…”
Section: Progressive Addition Lenses Developed For Myopia Treatmentmentioning
confidence: 99%